Pengaruh Waktu Aplikasi 2,2-Dimethylhydrazide terhadap Pertumbuhan dan Pembungaan Tanaman Krisan (Chrysanthemum morifolium Ramat) - Rezi Nurrahmadani; Irawati Irawati (Program Studi Agroteknologi Fakultas Pertanian Universitas Andalas, 2017)
An experiment aimed at determining the best time of application of 2,2-dimethylhydrazideto promnote the growth and flowering inchrysanthemum(Chrysanthemum morifolium Ramat) and shortened the flower stalk to meet a standard as potted ornamental plant has been conducted from Agustus to December 2015. The experiment was carried out in a Greenhouse of Center for Technology Transfer and Regional Development for Agriculture, Alahan Panjang, West Sumatra. A Completely Randomised Design with 5 treatments and 4 replicates was assigned. Data were analysed with analysis of variance and mean comparisons of DNMRT at 5% level. Data indicated that the best time to apply was 2,2-dimethylhydrazide at 3 and 5 weeks after transplanting. The application of 2,2-dimethylhydrazide affected plant height, number of leaves, leaf length, leaf width, number of flowers, and flower diameter of chrysanthemum.